Thickness cortex mandible on Toraja viewed from women's groups radiographic panoramic - Irene E. Rieuwpassa; Asmawati Asmawati (Journal of Dentomaxillofacial Science, 2018)
Objective: This study aims to collect data on the mandibular cortical thickness of the woman inhabitants in the Toraja tribe.Material and Methods: The subjects of this study that underwent panoramic radiography were vulnerable women aged 45-90 years from the Toraja tribe. The technique used to assess cortical thickness was the measurement Mental Index (MI) by panoramic radiography. Results: MI detected a reduction in bone mass density in elderly women using panoramic radiography. Conclusion: Osteoporosis can be detected by measuring the MI using panoramic radiographs. This has been developed to detect osteoporosis.